UNDERSTANDING CUSTOMER ACCEPTANCE TO FINANCIAL TECHNOLOGY; STUDY IN INDONESIA (International Journal of Innovative Technologies in Economy, 2021)
In the Era of Digital 4.0, technology is of undeniable importance to any industry, including banking and finance. The disruption of technology and economic crisis has brought us the innovation of financial technology which is now mushrooming throughout the world. Financial Technology is an instrumental tool for financial inclusion thus has a big potential value in countries such as Indonesia. However, the acceptance of this new way of financial alternative still leaves a huge area for investigation. Especially in the acceptance of this technology as an alternative to conventional way of doing financial investment.The article is trying to investigate the acceptance of the financial technology sector to customers and the intention to use it in the future. The research found that the minimal effort and the availability of resources that facilitate contribute greatly to the acceptance of financial technology to the users. Furthermore, the result implies that social factors, hedonic motivation and habits have no significant effect on the intention of adapting this new way of doing financial activities.